2017
DOI: 10.3390/ma10060643
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Caries Effects of Dental Adhesives Containing Quaternary Ammonium Methacrylates with Different Chain Lengths

Abstract: The objectives of this study were to investigate the effects of dental adhesives containing quaternary ammonium methacrylates (QAMs) with different alkyl chain lengths (CL) on ecological caries prevention in vitro. Five QAMs were synthesized with a CL = 3, 6, 9, 12, and 16 and incorporated into adhesives. Micro-tensile bond strength and surface charge density were used to measure the physical properties of the adhesives. The proportion change in three-species biofilms consisting of Streptococcus mutans, Strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 41 publications
1
48
0
3
Order By: Relevance
“…This fact gives these polymers ultra-hydrophilicity and consequently great hydration ability [70,71]. Studies concerning surface modification with zwitterionic polymers have proved to be a promising strategy to reduce microorganisms' adhesion [72,73]. Very recently, a study using a tyramine-conjugated sulfobetaine polymer, grafted on polyurethane showed a great reduction in S. aureus adhesion to the surface [74].…”
Section: Chemical Modificationmentioning
confidence: 99%
“…This fact gives these polymers ultra-hydrophilicity and consequently great hydration ability [70,71]. Studies concerning surface modification with zwitterionic polymers have proved to be a promising strategy to reduce microorganisms' adhesion [72,73]. Very recently, a study using a tyramine-conjugated sulfobetaine polymer, grafted on polyurethane showed a great reduction in S. aureus adhesion to the surface [74].…”
Section: Chemical Modificationmentioning
confidence: 99%
“…This unique antibacterial mechanism made QAMs effective against a wide range of microbes and also minimized the possibility of the development of resistance by microbes. Two recently developed QAM compounds, dimethylaminododecyl methacrylate (DMADDM) and dimethylaminohexadecyl methacrylate (DMAHDM), were proven to be more effective than conventional QAMs [11][12][13][14][15][16][17]. The resistance against aging is an added benefit of these novel compounds which makes them remain active for a longer duration and inhibit bacterial colonization.…”
Section: Introductionmentioning
confidence: 99%
“…A cárie secundária é a principal causa para substituição de restaurações (3,5,6,12,23,24,26,27,34,36,40,41). Esta é uma doença infecciosa sacarosedependente que ocorre em interfaces previamente restauradas(42) e os microrganismos responsáveis pelo seu surgimento são os mesmos envolvidos na cárie primária (42).…”
Section: Cárie Secundáriaunclassified
“…Diante de uma odontologia minimamente invasiva e cada vez mais conservadora, é preconizada a remoção da dentina infectada e a dentina afetada é deixada no fundo da cavidade, o que pode resultar em bactérias residuais após preparo cavitário (3, 5, 23, 24, 26, 34, 36, 45-47, 51, 52). É estimado que de 50 a 70% dos procedimentos restauradores ocorrem para substituição de restaurações deficientes, devido a presença de cáries secundárias (12,23,24,26,47). Então, lançar mão de mecanismos que possam inibi-las torna-se primordial para promover maior longevidade das restaurações diretas em resina composta.…”
Section: Cárie Secundáriaunclassified
See 1 more Smart Citation